Transparansi dan Akuntabilitas: Kunci Utama dalam Membangun Kepercayaan Muzaki terhadap LAZIS - Apriyansyah, Roli (Forum Kerjasama Pendidikan Tinggi, 2024)
This study aims to address whether the transparency and accountability of financial reports influence the trust level of muzaki (zakat donors) in the zakat, infaq, and shadaqah management institutions (LAZIS) in Mataram City. The research employs a quantitative approach using primary data sources. Primary data were collected through the distribution of questionnaires both online and offline to muzaki who pay zakat through LAZIS, managed either by the government or private entities in Mataram City. The sampling method used was probability sampling, with a total of 100 respondents. The data analysis technique utilized was multiple linear regression analysis. The results demonstrate that the transparency and accountability of financial reports have a positive impact on the trust level of muzaki in Mataram City, with financial report transparency being the most dominant variable influencing the trust level.